The analysis of development of the SME sector in the Republic of Serbia - Milanović Mirko (Trendovi u Poslovanju)
There is growing evidence around the world that the sector of small, medium enterprises and entrepreneurs (SMEs) has a very important role in the economic development of any country, whether it is about countries with developed economies, developing countries or countries in transition. In the Republic of Serbia, the sector of small, medium enterprises and entrepreneurs (SMEs) is also a very important factor in economic development. Today, this sector has a tendency to make more use of intensive production processes than large companies and thus significantly contribute to increased employment, income generation and poverty reduction. The paper deals with the analysis of the development of the SME sector in the Republic of Serbia with special reference to the period from 2015-2017.